2018
DOI: 10.1111/tbj.12977
|View full text |Cite
|
Sign up to set email alerts
|

Does response to neo-adjuvant chemotherapy impact breast reconstruction?

Abstract: Neo-adjuvant chemotherapy (NAC) is administered in breast cancer treatment for downstaging of disease. Here, we determined the impact of response to NAC on breast reconstruction uptake. A prospective NAC and mastectomy database with or without reconstruction were reviewed with IRB approval. Univariable analyses were conducted using Kruskal-Wallis or Fisher's exact tests. Multivariable logistic regression was used to adjust for potential confounders. We identified 271 patients with unilateral breast cancer rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…During this study, we examined factors influencing the type of IR surgery after NAC. Our findings indicated that younger age and earlier tumor and nodal stages at presentation were correlated with IR after NAC, which was consistent with the findings of some previous studies 15 . Because the pathological tumor stage was significantly associated with IR, and because the pathological nodal stage and total pCR were not, we speculated that the response of the primary site after NAC was more important to the choice of IR than that of the axillary nodes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…During this study, we examined factors influencing the type of IR surgery after NAC. Our findings indicated that younger age and earlier tumor and nodal stages at presentation were correlated with IR after NAC, which was consistent with the findings of some previous studies 15 . Because the pathological tumor stage was significantly associated with IR, and because the pathological nodal stage and total pCR were not, we speculated that the response of the primary site after NAC was more important to the choice of IR than that of the axillary nodes.…”
Section: Discussionsupporting
confidence: 92%
“…Because the pathological tumor stage was significantly associated with IR, and because the pathological nodal stage and total pCR were not, we speculated that the response of the primary site after NAC was more important to the choice of IR than that of the axillary nodes. During a study of patients treated at Memorial Sloan Kettering Cancer Center, Cassidy et al revealed that neither conversion from clinically node-positive to clinically node-negative nor pCR was associated with increased rates of IR 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations